Development of global temperature and pH calibrations based on bacterial 3-hydroxy fatty acids in soils - Vequaud, P.; Derenne, S.; Thibault, A.; Anquetil, C.; Bonanomi, G.; Collin, S.; Contreras, S.; Nottingham, A.T.; Sabatier, P.; Salinas Revilla, N.; Scott, W.P.; Werne, J.P.; et al. (Copernicus GmbH, 2021)
Abstract. Gram-negative bacteria produce specific membrane lipids, i.e. 3-hydroxy fatty acids with 10 to 18 C atoms. They have been recently proposed as temperature and pH proxies in terrestrial settings. Nevertheless, the existing correlations between pH or temperature and indices derived from 3-OH FA distribution are based on a small soil dataset (ca. 70 samples) and only applicable regionally. The aim of this study was to investigate the applicability of 3-OH FAs as mean annual air temperature (MAAT) and pH proxies at the global level. This was achieved using an extended soil dataset of 168 topsoils distributed worldwide, covering a wide range of temperatures (5 to 30 ∘C) and pH (3 to 8). The response of 3-OH FAs to temperature and pH was compared to that of established branched glycerol dialkyl glycerol tetraether (GDGT)-based proxies (MBT'5Me/CBT). Strong linear relationships between 3-OH-FA-derived indices (RAN15, RAN17 and RIAN) and MAAT or pH could only be obtained locally for some of the individual transects. This suggests that these indices cannot be used as palaeoproxies at the global scale using simple linear regression models, in contrast with the MBT'5Me and CBT. However, strong global correlations between 3-OH FA relative abundances and MAAT or pH were shown by using other algorithms (multiple linear regression, k-NN and random forest models). The applicability of the three aforementioned models for palaeotemperature reconstruction was tested and compared with the MAAT record from a Chinese speleothem. The calibration based on the random forest model appeared to be the most robust. It generally showed similar trends with previously available records and highlighted known climatic events poorly visible when using local 3-OH FA calibrations. Altogether, these results demonstrate the potential of 3-OH FAs as palaeoproxies in terrestrial settings.
Keywords: Transect; Soil water; Chemistry; Linear regression; Environmental chemistry; Air temperature; Calibration; Environmental science; Soil science; Atmospheric sciences; Ecology; Mathematics; Geology; Statistics; Biology; https://purl.org/pe-repo/ocde/ford#1.05.08